Psychological Well-Being in Adolescents: Personal Traits and Family Relationships (The Review of Foreign Researches) - T.A. Zhdanova; E.V. Filippova (Современная зарубежная психология)
The review is focused on results of recent investigations concerned with the problem of psychological well-being and elucidation of main factors of psychological well-being formation in adolescents. Different approaches to the study of the concept of psychological well-being, both domestic and foreign are listed. A major emphasis of review is placed on links between psychological well-being and personal traits as well as family relationships. The analyzed papers pay special attention to such personal traits as perfectionism and mindfulness as an ability to realize and reflect one’s own activity. It was shown that psychological well-being positively correlated with mindfulness, self-compassion, cognitive flexibility, and negatively correlated with high scores of perfectionisms. Some investigations present new important data about effects of conflicts between children and parents on adolescents’ well-being. Psychotherapeutic roles of grandmothers and grandfathers in life of adolescents are analyzed, particularly in dysfunctional families. The common position of the set of analyzed papers is the assertion of necessity to investigate effects of family on adolescents’ psychological well-being, regarding a family, including all its members belonging to all generations, as a whole.